The efficacy of sodium azulene sulfonate L-glutamine for managing chemotherapy-induced oral mucositis in cancer patients: a prospective comparative study - Satoru Nihei; Junya Sato; Hideaki Komatsu; Kazushige Ishida; Toshimoto Kimura; Takashi Tomita; Kenzo Kudo (BMC, 2018)
Abstract Background The efficacy of sodium azulene sulfonate L-glutamine (GA) in treating oral mucositis caused by the administration of anticancer agents has not been previously elucidated. Therefore, this prospective comparative study was conducted to evaluate the efficacy of GA in treating oral mucositis caused by chemotherapy regimens involving fluorinated pyrimidine anticancer drugs. Methods The subjects of this study were patients with oral mucositis of grade 2 or higher while on outpatient chemotherapy regimens involving fluorinated pyrimidine anticancer drugs for colorectal or breast cancer. The subjects were randomly divided into a group that received GA (the GA group) or a group that did not receive GA (the control group) by using the closed-envelope method. GA was administered three times a day every day from the first day of the regimen until the final day. The primary endpoint was the development of oral mucositis of grade 2 or higher. The secondary endpoint was the severity of oral pain, which was judged using an 11-stage numerical rating scale (NRS) ranging from 0 to 10. Results The proportion of patients with oral mucositis of grade 2 or higher was 32.4% in the GA group and 57.6% in the control group. The GA group had a significantly lower frequency of occurrence. The changes in the NRS scores before and after the trial began were − 2.9 ± 0.6 in the GA group and − 1.2 ± 0.5 in the control group. The NRS score decreased more significantly in the GA group than in the control group (P = 0.046). One patient stopped GA treatment voluntarily due to nausea; other than nausea, no GA-related side effects were observed. Conclusions GA protects against oral mucositis and reduces the severity of prevailing oral mucositis symptoms. Our findings indicate that GA is a highly safe and convenient drug.